1994
DOI: 10.1097/00007890-199408270-00003
|View full text |Cite
|
Sign up to set email alerts
|

Modified Simple Cold Storage of Rat Livers With Uw Solution

Abstract: Rat livers were preserved with the conventional use of UW solution for 30, 42, and 48 hr and compared with livers in which the vascular bed was expanded with an additional 10 to 60 ml UW/ 100 g liver. The extra UW, expressed as % liver weight, was entrapped during final portal infusion by tying off the supra-and infrahepatic inferior vena cava. A beneficial influence of the vascular expansion was most pronounced in the 40% group, with 10/10, 5/10, and 3/10 long-term survivors following transplantation after 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…As early as in the 1980s an effective blood washout was thought to be mandatory to improve the organ outcome after transplantation (3,18). Procurement studies in man, however, have not been able to demonstrate significant differences in the methods used for initial perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as in the 1980s an effective blood washout was thought to be mandatory to improve the organ outcome after transplantation (3,18). Procurement studies in man, however, have not been able to demonstrate significant differences in the methods used for initial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Slices were preserved in UW-CSS supplemented with 3 mmol/L fresh glutathione, for a period of 0-, 24-or 48-h cold storage. These time points were chosen based on survival results of rat liver transplantation experiments (13,17,18), revealing that 0-h preservation in UW-CSS resulted in 100% survival, 24 h in 20-50% and 48 h in 0% animal survival. After preservation, 50% of the slices were reperfused, while the other half were immediately analyzed (Table 1).…”
Section: Preservationmentioning
confidence: 99%
“…31 Using a microfil perfusion technique, we have previously shown that microcirculatory damage is augmented after graft reperfusion causing stagnation, pooling, and a filling-defect in the sinusoids, as well as a reduction in hepatic blood flow, particularly in arterial flow. 32 Studies aimed at expanding the microvasculature during liver preservation 33 or modulation of vasoactive substances 34 were shown to improve hepatic blood flow, ICG elimination, and graft function after reperfusion. Further study on the role of hepatic blood flow in the determination of K ICG levels and posttransplant graft function is needed.…”
mentioning
confidence: 99%
“…In addition, the inherited sinusoidal disturbance in steatotic livers may lead to inadequate perfusion with preservation solution during organ retrieval and subsequent suboptimal protection of the graft throughout the cold storage. In normal rat livers a method of vascular bed expansion (VBE), which was established during prolonged cold storage, was shown to improve subsequent graft reperfusion and function [8]. Apart from the uniform exposure of the entire graft to the UW solution, VBE was thought to prevent sinusoidal collapse by expanding the hepatic microvasculature, which subsequently led to decreased resistance for the reperfusion blood flow [8].…”
Section: Introductionmentioning
confidence: 99%
“…In normal rat livers a method of vascular bed expansion (VBE), which was established during prolonged cold storage, was shown to improve subsequent graft reperfusion and function [8]. Apart from the uniform exposure of the entire graft to the UW solution, VBE was thought to prevent sinusoidal collapse by expanding the hepatic microvasculature, which subsequently led to decreased resistance for the reperfusion blood flow [8]. We hypothesized that VBE pretreatment in steatotic rat liver grafts would attenuate hepatic injury and improve graft viability and function subsequent to revascularization.…”
Section: Introductionmentioning
confidence: 99%